Institutionalization in the Asia Indigenous Peoples Pact - Tharu, Prem Singh (Technical Centre for Agricultural and Rural Cooperation, 2019)
The environmental and agricultural practices of indigenous people in South East Asia are being threatened by aggressive developments, which exploit their natural resources and displace them from their ancestral land and territories. The Asia Indigenous Peoples pact is using experience capitalization processes to share many innovative experiences, all of which are successfully helping indigenous people fight for their rights.